Pengaruh Kompetensi Terhadap Produktivitas Kerja Karyawan Di Rumah Sakit Pertamina Jaya - Lia Marthalia; Anisah Anisah (Postgraduate of Jayabaya University, 2020)
The aims of this research to analyze and examine the effect of competency on work productivity for employee at Pertamina Jaya Hospital. This study used quantitative research methods associative survey using correlation analysis techniques. The population in this study were all employees of Pertamina Jaya Hospital and consisting of one hundred twenty-two employees. The data we collected separately by the respondents filling some questioners. The correlation technique was applied to analyze the data which had been previously treated with the regression and correlation procedure. The results showed that the influence of discipline on work productivity to possess the most powerful contribution of 69.50%, while 30.50% is determined by other factors that are not included in this research. The implications of this study indicate that the application of high competency and good discipline will improve the work productivity of the employees.